Quality of life X quantity of life: The right to die with dignity protected by the advanced directives institutes - Deserti, Bruna Sitta [UNESP]; Veiga, Hélio [UNESP]; Marchetto, Patrícia Borba [UNESP]; Corona, Roberto Brocanelli [UNESP]; Lamenha Gomes, Thiago Soares (My University, 2015)
In the last century we have witnessed a great development in medicine. New drugs and sophisticated surgical interventions present the proposal for a long life, almost as a product available on the market. Facing death as a natural process is increasingly distant from people's lives nowadays. Quantity of life does not mean quality of life. In cases of incurable diseases, the best treatment is to accept the condition and offer palliative cares to ensure the quality of life that still remains. It cannot be forgotten that behind all the medical techniques in development there are human beings who ought to be at the center of the medical-patient relation and have their dignity and autonomy respected. There is a juridical mechanism called Advanced Directives, popularly known as Living Will, which is a public document to register all the medical directions regarding health care treatments and procedures that the patients do not wish to be submitted to, that can be used to ensure that the patients wishes concerning his life will be respected when he may not be able to express his will. The advanced directives defend the dignity of every human being and the palliative cares rather than the pursuit of a cure.
Keywords: Advanced directives; Health; Living will; Quality of life; Quantity of life